THE ROLE OF NOTE-TAKING IN CONSECUTIVE INTERPRETING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Note-taking plays a crucial role in consecutive interpreting, serving as a bridge between comprehension and reproduction of the source speech. This paper explores the importance, techniques, and functions of note-taking in the interpreting process. It highlights how structured notes enable interpreters to retain key ideas, logical connections, and speaker intentions while minimizing memory overload. The study also discusses various models of note-taking, such as symbols, abbreviations, and structural cues that assist interpreters in delivering accurate and coherent renditions. Furthermore, it emphasizes the relationship between effective note-taking and interpreter training, suggesting that systematic practice can significantly improve interpreting quality. Overall, the paper concludes that note-taking is not merely a mechanical act but a cognitive strategy that enhances understanding, concentration, and fidelity in consecutive interpreting.